The equity premium and the concentration of aggregate shocks - Mankiw, N.Gregory (Journal of Financial Economics, 1986)
This paper examines an economy in which aggregate shocks are not dispersed equally throughout the population. Instead, while these shocks affect all individuals ex ante, they are concentrated among a few ex post. The equity premium in general depends on the concentration of these aggregate shocks; it follows that one cannot estimate the degree of risk aversion from aggregate data alone. These findings suggest that the empirical usefulness of aggregation theorems for capital asset pricing models is limited.